Metadata and semantic research 5th International Conference, MTSR 2011, Izmir, Turkey, October 12-14, 2011. Proceedings - García-Barriocanal, Elena; Cebeci, Zeynel; Okur, Mehmet C.; Ozturk, Aydin (Communications in Computer and Information Science, 2011)
This volume constitutes the selected papers of the 5th International Conference on Metadata and Semantic Research, MTSR 2011, held in Izmir, Turkey, in October 2011. The 36 full papers presented together with 16 short papers and project reports were carefully reviewed and selected from 118 submissions. The papers are organized in topical sections on Tracks on Metadata and Semantics for Open Access Repositories and Infrastructures, Metadata and Semantics for Learning Infrastructures, Metadata and Semantics for Cultural Collections and Applications, Metadata and Semantics for Agriculture, Food and Environment.